The Effect of the Leaderless Group Discussion (LGD) Method on the Value of Professional Ethics as a Result of the Internship Program at SEAMEO RECFON - Suswandi, Dodi; Hasanah, Laeli Nur (Enrichment: Journal of Multidisciplinary Research and Development, 2024)
This study aims to determine how much influence the learning of the internship program with the Leaderless Group Discussion (LGD) Method has on the Professional Ethics Value of the Internship Program at SEAMEO RECFON. The research method used in this research is Pre- Experimental Design using the One-Shot Case Study Design type. The sample used in this study were students of the Internship Program and Certified Independent Study (MSIB) Batch 6, totaling 30 Internship Participants. In this study, the average (mean) of the results of the participant activity observation sheet was 79% with the criteria “Very Good”, this shows that students play an active role in participating in the internship program with the Leaderless Group Discussion (LGD) method. As for the learning outcomes of students, the average (mean) of the results of professional ethics scores was 80 with the criteria “Excellent”, this shows that the students' internship program is in excellent criteria after getting treatment (treatment) in the form of the Leaderless Group Discussion (LGD) Method. Based on the results of the calculation of research data, it can be concluded that there is an influence caused by learning an apprenticeship program with the Leaderless Group Discussion (LGD) Method on the Professional Ethics Value of the results of apprentices by 14.9%.